Synchronization Measure Based on a Geometric Approach to Attractor Embedding Using Finite Observation Windows. (8th August 2018) - Timofejeva, Inga; Poskuviene, Kristina; Cao, Maosen; Ragulskis, Minvydas
Abstract : A simple and effective algorithm for the identification of optimal time delays based on the geometrical properties of the embedded attractor is presented in this paper. A time series synchronization measure based on optimal time delays is derived. The approach is based on the comparison of optimal time delay sequences that are computed for segments of the considered time series. The proposed technique is validated using coupled chaotic Rössler systems.